The Use of Communicative Approach in Foreign Language Learning Through Listening Activity by Using Whatsapp Application - Tendiami, Anggia (English Language and Literature International Conference (ELLiC) Proceedings, 2017)
Listening is one of the four skills taught to learners in foreign language learning activity. Yet, it is no rarely found that students are sometimes uninterested in the listening activity caused by repeated same technique delivered by teacher in the classroom. Besides that, the interaction among students seems to be forgotten when the listening activity is conducted. This paper is about to explain and describe how the communicative approach is applied in the process of foreign language learning activity specifically in listening activity through the using of WhatsApp application as the means for communication. This technique is used in order to make students feel more lively when doing their activities in the classroom and allow for the interaction among them. As the part of technology, WhatsApp plays quite important role in this activity to motivate students to interact with their partners. The application of this method is implemented in a class consists of twelve basic-level foreign language learners and using the materials contained in their textbooks. Also, the teacher takes part in the activity to monitor and provide feedback to the result of the listening activity. By applying the communicative approach in the listening activity, teacher is expected to create an interesting learning atmosphere for students and allowing them to interact with each other. After the listening activity is conducted, questionnaires are distributed to see the response of the students telling their self-reflection regarding to this activity. As the result, besides improving the listening skill, students can also improve their communicative competence.